An Analysis of Derivational and Inflectional Morphemes in Song Lyrics on Taylor Swift’s “Fearless” Album - Nunik Nur Anikah; Susilawati Susilawati; Eline Rozaliya Winarto (National Conference on Language, Education, and Technology Proceeding, 2022)
Morphology is the study of morphemes. By studying morphemes, especially derivations, it can develop our English vocabulary because it generates new word classes and meanings. The purpose of this study was to determine the process of forming derivational and inflectional affixes and the types of derivational affix functions used in song lyrics on Taylor Swift’s “Fearless” album. Researcher used 3 songs, including: Love Story, You Belong With Me and Breathe. The approach of this research was descriptive qualitative research. The instrument used was the researcher as the main instrument and document analysis as the second instrument used to collect data. The subject of this reseach is the song lyrics on Taylor Swift’s “Fearless” album. The data of this study are all data containing affixes on Taylor Swift’s “Fearless” album. The researcher found 57 affixes; 53 inflections and 4 derivations. The inflection data were 5 –s third-person singular, 15 –ed past tense, 14 –ing progressive, 3 –en past participle, 15 –s plural and 1 –er comparative. Meanwhile, the derivation data were 1 noun to adjective, 2 adjective to adverb and 1 adjective to adjective. Then, the researcher found 2 types of derivation affix functions; adjective formation and verb formation.